"Like No One Is Listening to Me": A Qualitative Study of Patient–Provider Discordance Between Global Assessments of Disease Activity in Rheumatoid Arthritis. Issue 10 (4th September 2018) - Kvrgic, Zoran; Asiedu, Gladys B.; Crowson, Cynthia S.; Ridgeway, Jennifer L.; Davis, John M.
Abstract : Objective: To explore the perspectives and experiences of patients with rheumatoid arthritis (RA) whose assessments of their disease differ from those of their rheumatology care provider. Methods: A total of 20 adult RA patients with patient‐provider discordance at their most recent rheumatology appointment (within 4 weeks) were recruited. Discordance was defined by an absolute difference of 25 or more between patient and provider global assessments on a visual analog scale (VAS) of disease activity. For descriptive purposes, participants completed the Health Assessment Questionnaire II, pain VAS, and Patient Health Questionnaire 9 depression scale. Interviews were conducted in person and individually with each patient with a semistructured interview guide. Topics ranged widely, including participants' perspectives and experiences with living with RA, clinical disease assessments, patient‐provider communication, and psychosocial or other needs. Data from the interviews were analyzed using interpretive phenomenological analysis. Results: Six major themes emerged from the patient interviews describing patient‐provider discordance and disease assessment: being misunderstood by others, limitations of provider assessments, discrepancy with provider findings, inadequate active listening on the part of health care providers, unmet psychosocial needs, and lack of patient empowerment. Conclusion: Patients described discordance in terms of symptom assessment and understanding how RA affects everyday life. Typical clinical assessments did not capture their experience. The resulting conceptual framework should inform future interventional studies seeking to enhance concordance of patient‐physician communication and to optimize satisfaction with care and health‐related quality‐of‐life outcomes for patients with RA.